Presencia de Strongyloides stercoralis en un estudio sobre enteroparasitosis en escolares del asentamiento humano “La Candelaria”, distrito de Chancay, provincia de Huaral, departamento de Lima - Natividad Carpio, Ines (2024)
Introducction: the intestinal parasitoses are public health problems in Perú. Strongyloidiasis is the intestinal infection produced by the nematode Strongyloides stercoralis; it is endemic in Perú, with proven high prevalences in jungle and andean communities; its presence has been barely studied in coastal communities.Objetives: to determine the prevalence of Strongyloides stercoralis among the human enteroparasites in a coastal community in Perú.Materials and methods: a fecal sample was obtained from all willing participants in a health campaign that took place at the public school Virgen de la Candelaria at the community of La Candelaria, Chancay district, Huaral province. The samples were processed using 5 coprologic methods: direct examination, spontaneous tube sedimentation, rapid sedimentation technique modified by Lumbreras, Kato test, and Baermann technique modified by Lumbreras, to evaluate the presence of Strongyloides stercoralis and other enteroparasites.Results: 173 samples where collected. The prevalence of enteroparasitosis (any parasite or commensal) was 98%; that of pathogenic enteroparasites was 76%. S. stercoralis was found in 2 schoolchildren (1.1%).Conclusion: this study shows the high frequency of enteroparasites in general and indicates the presence of S. stercoralis in a coastal community of Perú.